Delevoping Bilingual Translators’ Competences - L Yu Mirzoyeva; O V Syurmen (Polylinguality and Transcultural Practices, 2018)
Kazakhstan is a multilingual country where dominant languages are Kazakh, the state language, and Russian, which is the language of communication between different ethnic groups. Due to a number of extra-linguistic factors most Kazakhs are bilinguals, with natural, productive and coordinative bilingualism. In our opinion bilingualism with such characteristics is a sustainable basis for developing competencies of translation from both languages. The aim of the article is to consider existing system of translator training and suggest recommendations on use of the advantages of language situation in Kazakhstan. Survey among employers, translation and tourist agencies as well as representatives of such companies as DHL, Turkish Airlines, AirAstana, Hamle, shows their interest in translators able to work both with English-Russian and English-Kazakh languagepairs. Notwithstanding the fact that language situation in Kazakhstan allows to trainspecialists in both languages, there are no educational programs for trainingtranslation students translate from both Kazakh and Russian. This brings up the question of developing special educational program for training bilingual translators.